The experiences of clients and healthcare providers regarding the provision of reproductive health services including the prevention of HIV and AIDS in an informal settlement in Tshwane - M.L.S. Mataboge; S. Beukes; A.G.W. Nolte (AOSIS, 2016)
Globally challenges regarding healthcare provision are sometimes related to a failure to estimate client numbers in peri-urban areas due to rapid population growth. About one-sixth of the world's population live in informal settlements which are mostly characterised by poor healthcare service provision. Poor access to primary healthcare may expose residents of informal settlement more to the human immunodeficiency virus (HIV) and to acquired immunodeficiency syndrome (AIDS) than their rural and urban counterparts due to a lack of access to information on prevention, early diagnosis and treatment. The objective of this study was to explore and describe the experiences of both the reproductive health services' clients and the healthcare providers with regard to the provision of reproductive health services including the prevention of HIV and AIDS in a primary healthcare setting in Tshwane. A qualitative, exploratory and contextual design using a phenomenological approach to enquire about the participants' experiences was implemented. Purposive sampling resulted in the selection of 23 clients who used the reproductive healthcare services and ten healthcare providers who were interviewed during individual and focus group interviews respectively. Tesch's method for qualitative data analysis was used. Ethical principles guided the study, and certain strategies were followed to ensure trustworthiness. The findings revealed that females who lived in informal settlements were aware of the inability of the PHC setting to provide adequate reproductive healthcare to meet their needs. The HCPs acknowledged that healthcare provision was negatively affected by policies. It was found that the community members could be taught how to coach teenagers and support each other in order to bridge staff shortages and increase health outcomes including HIV/AIDS prevention.